Socio-Economic Determinants of Sexually Transmitted Infections among Adolescents in Egbeda Local Government Area, Oyo State (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Introduction: Sexually transmitted infections (STIs) represent a significant public health concern among adolescents globally, particularly in sub-Saharan Africa. In Nigeria, the prevalence of STIs among adolescents is rising, primarily due to risky sexual behaviors influenced by various sociodemographic and economic factors. Adolescents' knowledge about STIs is pivotal in mitigating their exposure to these infections. Understanding the relationship between sociodemographic characteristics and STI knowledge is critical in designing effective intervention strategies.ObjectivesThis study aimed to assess the level of STI knowledge among adolescents in Egbeda Local Government Area, Nigeria, and to explore the sociodemographic factors influencing their awareness of STIs. The study also sought to determine the association between economic factors and adolescents' sexual health behaviors.Method of AnalysisA cross-sectional study design was employed, targeting adolescents aged 10 to 19 years in secondary schools across the Egbeda Local Government Area. Data were collected through structured questionnaires, which assessed participants’ knowledge of STIs, sexual behaviors, and socioeconomic backgrounds. The data were analyzed using descriptive statistics, Chi-square tests, and correlation analysis to examine the relationships between sociodemographic variables and STI knowledge levels.ResultsThe study found that 53.3% of adolescents exhibited high knowledge of STIs, while 30% had moderate knowledge and 16.7% had low knowledge. Gender, age, parental education, and occupation were significantly associated with the level of STI knowledge. Females (p = 0.037) and older adolescents (p = 0.029) were more likely to have high knowledge levels. Parental education also played a crucial role, with adolescents whose parents had tertiary education displaying higher STI knowledge (p = 0.015). Economic factors, such as parental occupation, were linked to the adolescents' sexual health knowledge, with those from higher-income backgrounds having better knowledge and engaging in safer sexual practices.ConclusionThe findings emphasize the importance of sociodemographic factors in shaping adolescents’ STI knowledge. Educational interventions targeting adolescents in lower socioeconomic settings and those with less educated parents are crucial. It is essential to incorporate age-appropriate, culturally sensitive sexual health education into the school curriculum and community-based programs. Furthermore, strategies should include involving parents and addressing economic barriers to ensure equitable access to sexual health resources. This study calls for a comprehensive approach to adolescent sexual health education to reduce the prevalence of STIs and promote informed sexual behaviors.